2016
DOI: 10.1016/j.joa.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Report of periprocedural oral anticoagulants in catheter ablation for atrial fibrillation: The Japanese Catheter Ablation Registry of Atrial Fibrillation (J‐CARAF)

Abstract: BackgroundTo obtain a perspective of the current status of catheter ablation for the cure of atrial fibrillation, the Japanese Heart Rhythm Society conducted a nationwide survey: the Japanese Catheter Ablation Registry of Atrial Fibrillation. In this report, we aimed to evaluate the periprocedural use of direct oral anticoagulants with respect to thromboembolic or bleeding complications.MethodsUsing an online questionnaire, the Japanese Heart Rhythm Society requested electrophysiology centers in Japan to regis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 21 publications
3
7
0
Order By: Relevance
“…In earlier studies, uninterrupted warfarin was superior to an interrupted oral anticoagulant strategy for the outcome of AF ablation [10][11][12]. DOACs have been shown to be comparatively useful as warfarin as a periprocedural oral anticoagulant [4,[13][14][15][16]. In the present survey, the rate of warfarin use increased in the sequential order from PE[-] to critical PE, noncritical PE being intermediate, while the rate of DOAC use decreased in the same order.…”
Section: Interpretation Of the Present Resultssupporting
confidence: 45%
See 1 more Smart Citation
“…In earlier studies, uninterrupted warfarin was superior to an interrupted oral anticoagulant strategy for the outcome of AF ablation [10][11][12]. DOACs have been shown to be comparatively useful as warfarin as a periprocedural oral anticoagulant [4,[13][14][15][16]. In the present survey, the rate of warfarin use increased in the sequential order from PE[-] to critical PE, noncritical PE being intermediate, while the rate of DOAC use decreased in the same order.…”
Section: Interpretation Of the Present Resultssupporting
confidence: 45%
“…To achieve efficacious and safe treatment of various arrhythmias, technological and technical innovations of catheter ablation are constantly being introduced into practice. To assess whether catheter ablation for the cure of atrial fibrillation (AF) is appropriately Contents lists available at ScienceDirect journal homepage: www.elsevier.com/locate/joa performed in Japan, the Japanese Heart Rhythm Society (JHRS) started the annual nationwide registry of patients who underwent catheter ablation for AF: the Japanese Catheter Ablation Registry of Atrial Fibrillation (J-CARAF) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…The present results are consistent with the findings of a recent nationwide survey of CA for AF conducted in Japan (J-CARAF) by the Japanese Heart Rhythm Society [34]. In J-CARAF, 4698 patients were administered warfarin or a DOAC up to the day before AF ablation, and 64.2% of patients had paroxysmal AF [34]. These findings are also in accordance with the current AF management guideline [10] and previous reports [9,[11][12][13][14][15].…”
Section: Discussionsupporting
confidence: 92%
“…The present results showed that there were significantly more patients with paroxysmal AF in the CA group than in the No-CA group (72.9% vs 38.9%), comprising almost two-fold the number of patients with paroxysmal AF in the No-CA group. The present results are consistent with the findings of a recent nationwide survey of CA for AF conducted in Japan (J-CARAF) by the Japanese Heart Rhythm Society [34]. In J-CARAF, 4698 patients were administered warfarin or a DOAC up to the day before AF ablation, and 64.2% of patients had paroxysmal AF [34].…”
Section: Discussionsupporting
confidence: 91%
“…We read with great interest the article by Murakawa et al [1] titled, “ Report of periprocedural oral anticoagulants in catheter ablation for atrial fibrillation: The Japanese Catheter Ablation Registry of Atrial Fibrillation (J-CARAF). ” The authors concluded that the choice of a novel oral anticoagulant (NOAC) as a periprocedural anticoagulant did not significantly alter the incidence of serious complications, compared with uninterrupted warfarin.…”
Section: Dear Editormentioning
confidence: 99%